2020
DOI: 10.1371/journal.pone.0227265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of viral disease hypophagia on pig jejunal function and integrity

Abstract: Pathogen challenges are often accompanied by reductions in feed intake, making it difficult to differentiate impacts of reduced feed intake from impacts of pathogen on various response parameters. Therefore, the objective of this study was to determine the impact of Porcine Reproductive and Respiratory Syndrome virus (PRRSV) and feed intake on parameters of jejunal function and integrity in growing pigs. Twenty-four pigs (11.34 ± 1.54 kg BW) were randomly selected and allotted to 1 of 3 treatments (n = 8 pigs/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Previous studies indicated that PRRSV infection impairs the lungs and intestine [ 17 ] and affects jejunal function and integrity due to hypophagia [ 18 ]. However, its impact on intestinal barrier function and the correspond mechanism of intestinal barrier injury remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that PRRSV infection impairs the lungs and intestine [ 17 ] and affects jejunal function and integrity due to hypophagia [ 18 ]. However, its impact on intestinal barrier function and the correspond mechanism of intestinal barrier injury remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, increased glucose removal from the plasma pool [ 25 , 78 ], a shift in glucose transporter expression [ 79 ], and the depletion of glycogen stores [ 43 ] may increase glucose availability to immune cells to some degree. A reduced energy demand from the digestive tract following hypophagia, as reflected by reduced cell migration and turnover [ 80 , 81 ], may also increase glucose availability for other tissues. In total, however, the contribution of glucogenic C by these adaptations is expected to be low in dairy cows during early lactation, as glycogen depots are generally exhausted after calving [ 82 , 83 ], while homeostasis of plasma glucose is tightly regulated [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the reduction in feed efficiency observed in non-vaccinated pigs was not observed in vaccinated pigs. These data suggest that vaccination prevents disease associated losses in feed efficiency and reductions in growth were largely due to reduced feed intake [ 13 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin slides were also used to evaluate intestinal morphology. Images were taken at 4 × magnification using a DP80 Olympus Camera mounted on an OLYMPUS BX 53/43 microscope (Olympus Scientific, Waltham, MA, USA), and 15 well orientated villus and crypt pairs (ileum) or 15 crypts (cecum and colon) were measured using OLYMPUS CellSens Dimension 1.16 software (Olympus Scientific) as previously described [ 13 ].…”
Section: Methodsmentioning
confidence: 99%